Methods for developing the creative abilities of preschool children based on music therapy - Konurova Leyla Ruslanovna (Zien Journals, 2025)
The topic of methods of creativity in children using music therapy is relevant in the modern educational and psychological context. Music, as a powerful tool of influence, can stimulate emotional development, improve cognitive functions and develop creative abilities. This paper discusses the main methods of music therapy aimed at developing creative skills in children. Emphasis is placed on improvisational techniques as well as the integration of music with other art forms such as dance and drama. Music therapy helps children express emotions, develop fantasy and imagination, and improve attention and memory. The study also examines the impact of music therapy on the development of social adaptation and interpersonal skills in children. The use of these methods contributes to the harmonious development of the child’s personality, the disclosure of his creative potential and overcoming possible psychological barriers.
Keywords: music therapy; creativity; child development